PENGARUH RETURN ON EQUITY, LABA PER SAHAM DAN NET PROFIT MARGIN PADA HARGA SAHAM PT. GUDANG GARAM TBK PERIODE 2004-2013 - Suryani Toha; Atikah Atikah; Anisah Anisah (Universitas Batanghari Jambi, 2014)
The main goal for investors was the company's performance in boosting the stock price, the stock price is an important indicator that must be considered by the company's management and investors to evaluate the success rate or the health of the company in the market capital. The data used are the highlights of finance PT Gudang Garam Tbk 2004-2013. The variables of this research consists of the return on equity (X 1), earnings per share (X 2), and net profit margin (X 3) as the independent variable and the dependent variable as a stock price. The results of this research is the third independent variable influences the stock price significantly to together and partially does not have a significant influence on the price of the stock, it is evident from the results of the R square just 77.2% of the variation stock prices can be explained by variation in Return on Equity, Earnings Per share and Net Profit Margin, while 12.8% the rest is explained by factors outside of research.